2020
DOI: 10.1002/jor.24837
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis to monitor implant seating and early detect fractures in cementless THA: An in vivo study

Abstract: The initial stability of cementless total hip arthroplasty (THA) implants is obtained by an interference fit that allows osseointegration for a long term secondary stability of the implant. Yet, finding the insertion endpoint that corresponds to an appropriate initial stability is currently often based on a number of subjective experiences of the orthopedic surgeon, which can be challenging. In order to assist the orthopedic surgeons in their pursuit to find this optimal initial stability, this study aims to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…The variance in data distribution may be caused by the variation in PU foam-filled core of the wooden bone model. In both the in vitro and in situ study, the contact microphone recorded a remarkably low amount of ambient noise (e.g., talking, instruments/equipment bumping into each other) in relation to the hammer blow, shown as gaps in Figure 2c, also compared to, for example, ambient audio recording [19], which suggests that it can be a useful tool in the OR and not just limited to recording THA acoustic emissions. In all studies, the frequency peaks are clearly visible and can be isolated to analyze, for example, the peak energy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The variance in data distribution may be caused by the variation in PU foam-filled core of the wooden bone model. In both the in vitro and in situ study, the contact microphone recorded a remarkably low amount of ambient noise (e.g., talking, instruments/equipment bumping into each other) in relation to the hammer blow, shown as gaps in Figure 2c, also compared to, for example, ambient audio recording [19], which suggests that it can be a useful tool in the OR and not just limited to recording THA acoustic emissions. In all studies, the frequency peaks are clearly visible and can be isolated to analyze, for example, the peak energy.…”
Section: Discussionmentioning
confidence: 97%
“…Shibunama et al [14] used a contact microphone on the bone itself (n = 1) to pick up less ambient noise and suggested that their system can help determine the right stem size. Other similar arthroplasties involving acoustic analysis have been carried out recently in an in vitro femur setup [15,16], acetabulum setup (with force sensors) [17], (with non-contact audio microphone) [18], in silico femur setup [16] and in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
“…A surgeon’s ability to consistently ensure optimal initial intraoperative implant stability for his or her patients is crucial to assure satisfactory long-term fixation of primary and revision femoral implants in cementless total hip arthroplasty (THA) [1] . Previous research [2] [6] has shown that vibration methods are sensitive to changes that occur between bone and implant when contact is established during the insertion of the implant into the bone. These non-destructive vibration techniques have their origin in civil engineering where they are referred to as Structural Health Monitoring (SHM) techniques [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Most comprise a mechanism to attach the instrument to the implant (‘connector’) and a part on which actuation and acquisition can be performed (‘subsystem’). Goossens et al [5] investigated the sound that resulted from insertion hammer blows to monitor femoral implant seating. This article presents an alternative approach in which a non-destructive vibration excitation was applied to the system in between insertion hammer blows, while contact-based sensors captured the response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation